The emerging new architecture of financial regulation - Charles Goodhart (Goethe University Frankfurt, Center for Financial Studies (CFS), 2011)
Now is a good time to take stock of progress in the reform of financial regulation. Much has been happening. The monumental Dodd-Frank Act was passed by the US Congress in July 2010. The deliberations and conclusions of the Basel Committee on Banking Supervision (BCBS) and the Financial Stability Board (FSB) are being put to the G-20 Heads of State in Seoul in November. In the UK the Vickers Committee has been asked to report on the structure of the banking sector by summer 2011. Some have argued from time to time that the momentum of financial regulatory reform was being lost; it is now two full years since the catastrophe of autumn 2008, and little seems to have been finally agreed. In fact the reverse is nearer the truth. In view of the power and predominance of the USA, it makes little sense for the rest of the world to try to press ahead with plans for the achievement of international regulatory agreements until the Americans have come to some outline decisions. In Congress the reform of financial regulation was given second priority, after the reform of their health-care program, and this has now resulted in the Dodd-Frank Act. Following that, financial regulators around the globe now can, and will, press forward to agree and then to implement revised and reformed plans for financial regulation. The danger, as I shall try to document below, is not that enthusiasm and efforts for undertaking such reforms are dissipating and running into the sand, but rather that in several respects the proposed reforms are incomplete and/or partially misdirected.
urn:nbn:de:hebis:30-101941
Keywords: 330; Finanzmarkt; Regulierung; Internationaler Finanzmarkt; Finanzmarktkrise; Welt